Diagnostics of mechanical asphyxia – experience of foreign countries (literature review) - Yakovtsova, Iryna; Hurov, Olexandr; Nikonov, Vadym; Kursov, Sergii; Hladkykh, Dmytro; Danyliuk, Svitlana (ScienceRise: Medical Science, 2021)
The aim of this study is to establish modern, global trends in the diagnosis of mechanical asphyxia. Materials and methods: search and bibliographic method (theoretical analysis, systematization and classification of library catalogues, printed and electronic sources on mechanical asphyxia) from open anchor databases Scopus preview, Web of Science and using information retrieval systems Google Scholar, Open Ukrainian Citation Index (OUCI), ScienceDirect on the Internet. Results: mechanical asphyxia, as one of the most common types of violent death, ranks first among deaths from mechanical injuries. Its study is of great interest among medical scientists in various fields, especially for resuscitators and forensic experts. Establishing the causes of asphyxia, clinical and morphological manifestations, and the consequences that unfortunately most often lead to death. With the rapid development of society, science is also developing rapidly, and the latest sensitive methods of diagnosing diseases are emerging. However, unfortunately, in the post-Soviet space, the diagnosis of most pathological conditions, including asphyxia, is determined by experience and sensory organs, which are determined using instrumental research methods in compliance with the requirements of evidence-based medicine. Given the peculiarities of the pathophysiological processes of the asphyxiation state and their manifestations in the body, doctors should rely primarily on general knowledge about hypoxic and asphyxiation disorders, which are determined using instrumental research methods in compliance with the requirements of evidence-based medicine. Conclusions: at present, the diagnosis of asphyxia consists of many morphological features. Failure to take into account the state of the body, the presence of chronic diseases, and drug or alcohol intoxication at the time of asphyxiation complicate the diagnosis. Detection of individual clinical manifestations or morphological features does not allow asserting its lifelong origin. Therefore, it is necessary to use modern research methods that should expand the possibilities of forensic diagnosis of the viability of injuries in terms of evidence-based medicine and provide forensic experts with a scientific basis for their results. One such method is immunohistochemical, which is gaining popularity and consolidating its position in the EU, China, Japan and America. In addition, this method is well-established and widespread in morphological studies of differential diagnosis of tumours. Some scientific works prove the expediency of using the immunohistochemical method to solve the problems of forensic expert practice, which is an actual scientific and practical task